Strategi Promosi Umroh Plus Berbasis Kemitraan Holistik Sebagai Upaya Eksistensi Daya Saing KBIH - Hadi, Yuharso; Lukmasyah; Machrus, Ali (AL-UJRAH, 2025)
Abstract This research was conducted to address the challenges posed by the rapid development of information technology, which demands tour and travel companies to promote their products in innovative, creative, and effective ways. The impact of this technological advancement is particularly notable in the field of Hajj plus and Umroh, where the "plus" Umroh package, integrating worship activities with Islamic tours, is undergoing development. Consequently, the competition among businesses has intensified, not only in terms of product offerings but also through irrational price competition. considering these circumstances, there is a need to enhance the strategies for the "plus" Umroh package and holistik partnerships. The research employed a qualitative approach, utilizing field research as the primary methodology. Data collection methods included observation, interviews, and documentation. The collected data underwent processes of data reduction, data presentation, and drawing conclusions. Based on the research findings, it was observed that the "plus" pilgrimage package holds superior appeal due to its ability to combine the exploration of Islamic cultural history in each country with the experience of pilgrimage in the holy land. Additionally, the holistik partnership strategy was found to be effective when community leaders with influence and congregations were approached. To further enhance the industry, it is recommended to establish an association organization comprising Hajj plus and Umroh travel entities. This association can play a pivotal role in determining standardized costs for Umroh fees. Keywords: Strategy, Umroh "plus", Holistik Partnership